2016
DOI: 10.1002/lary.26396
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold‐free cartilage tissue engineering with a small population of human nasoseptal chondrocytes

Abstract: NA. Laryngoscope, 127:E91-E99, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…9 Recently, Chiu et al showed decreasing GAG content in both native and engineered septal cartilage from donors under age 65. 23 Our findings are consistent with these prior studies on septal cartilage, demonstrating that the age-related decrease in GAGs seen in younger patients continues into old age. In addition, we showed that a similar but slower age-related loss of GAGs occurs in auricular cartilage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…9 Recently, Chiu et al showed decreasing GAG content in both native and engineered septal cartilage from donors under age 65. 23 Our findings are consistent with these prior studies on septal cartilage, demonstrating that the age-related decrease in GAGs seen in younger patients continues into old age. In addition, we showed that a similar but slower age-related loss of GAGs occurs in auricular cartilage.…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al found similar reductions in GAG content using a histologic grading scale to analyze septal cartilage from younger donors . Recently, Chiu et al showed decreasing GAG content in both native and engineered septal cartilage from donors under age 65 . Our findings are consistent with these prior studies on septal cartilage, demonstrating that the age‐related decrease in GAGs seen in younger patients continues into old age.…”
Section: Discussionsupporting
confidence: 89%
“…The choice of stimulus is equally as important as the cell type used. Culture supplementation with GDF-5 and IGF-I, as well as bFGF and TGF-β2 was shown to increase the histological staining intensity of GAG and type II collagen content in scaffold-free human nasal chondrocyte-derived neocartilage [89,106,117]. The use of IGF-I and GDF-5 increased the thickness of engineered neocartilage 12-fold over the untreated control [106] in scaffold-free nasal neocartilage engineered from human septal chondrocytes.…”
Section: 3: Nasal Cartilage Tissue-engineeringmentioning
confidence: 94%
“…As a hyaline cartilage, septal cartilage expectedly shows abundant immunohistochemical staining of collagen II, particularly in the central zone compared to the superficial zone, and little staining for collagen I [87]. Septal cartilage also contains small amounts of collagen IX, X, and XI [29,87,89,90]. LLC also shows abundant immunohistochemical staining for collagen II and little staining for collagen I [87].…”
Section: 22: Biochemical Contentmentioning
confidence: 99%
See 1 more Smart Citation